PENGARUH KOMPETENSI DAN PENGALAMAN KERJA TERHADAP KUALITAS AUDIT INTERNAL PEMERINTAH (Studi Pada Inspektorat Kabupaten Sumbawa) - U Usman; Irwan Dwi Putra (Pusat Riset dan Publikasi, 2026)
The objective of this study is to determine the influence of competence and work experience on the quality of internal audits of public agencies in the Sumbawa County Inspectorate, both partially and simultaneously. This type of study is associative and aims to examine the influence of independent variables consisting of auditor competence (X1) and auditor work experience (X2) on the dependent variable—the quality of internal audits of public agencies (Y). The study uses quantitative data obtained directly from primary sources through questionnaires. The data sources were all 23 auditors of the Sumbawa County Inspectorate, selected using a non-random sampling method with a continuous sampling method. Multiple linear regression, partial hypothesis testing (t-test), simultaneous hypothesis testing (F-test), and testing the coefficient of determination (R²) were used to analyze the data. The results of the data analysis showed that auditor competence (X1) and auditor experience (X2) had a positive and significant impact on the quality of internal public audits in the Sumbawa District Inspectorate (Y), both partially and simultaneously. The impact of the variables of auditor competence (X1) and auditor experience (X2) on the quality of internal public audits in the Sumbawa District Inspectorate (Y) was 73.3%, while the remaining of 26.7% was due to other variables not considered in this study, such as auditor independence, objectivity, knowledge, and integrity.